Have we got the optimal treatment for refractory Kawasaki disease in very young infants? A case report and literature review - Lersch, Robert; Mandilaras, Guido; Schrader, Meike; Anselmino, Felicitas; Haas, Nikolaus A.; Jakob, André (Frontiers in Pediatrics, 2023)
A small group of patients with Kawasaki disease (KD) demonstrates resistance to standard therapy, putting them at high risk for an unfavourable prognosis, especially regarding coronary artery aneurysms. Although adding corticosteroids to first line i.v. Immunoglobulins (IVIG) is considered beneficial, and despite timely treatment initiation, very young infants in particular can present an unfavourable clinical course. We report on a 3-month-old boy with a clinically severe KD phenotype involving the early development of giant coronary artery aneurysms. Because of his poor response to the first course of IVIG and prednisolone we administered infliximab. His clinical condition improved thereafter and his temperature dropped. Inflammatory markers however did not recover completely, and he remained subfebrile. In addition, as the coronary artery dimensions deteriorated, a second IVIG course was applied and prednisolone continued at the initial dosage. Although fever and routine inflammatory parameters normalized, close follow-up investigations revealed both, still increasing coronary artery dimensions and renewed rise in inflammatory parameters